Conditions under which Arousal Does and Does Not Elevate Height Estimates - Storbeck, Justin (Public Library of Science, 2014)
We present a series of experiments that explore the boundary conditions for how emotional arousal influences height estimates. Four experiments are presented, which investigated the influence of context, situation-relevance, intensity, and attribution of arousal on height estimates. In Experiment 1, we manipulated the environmental context to signal either danger (viewing a height from above) or safety (viewing a height from below). High arousal only increased height estimates made from above. In Experiment 2, two arousal inductions were used that contained either 1) height-relevant arousing images or 2) height-irrelevant arousing images. Regardless of theme, arousal increased height estimates compared to a neutral group. In Experiment 3, arousal intensity was manipulated by inserting an intermediate or long delay between the induction and height estimates. A brief, but not a long, delay from the arousal induction served to increase height estimates. In Experiment 4, an attribution manipulation was included, and those participants who were made aware of the source of their arousal reduced their height estimates compared to participants who received no attribution instructions. Thus, arousal that is attributed to its true source is discounted from feelings elicited by the height, thereby reducing height estimates. Overall, we suggest that misattributed, embodied arousal is used as a cue when estimating heights from above that can lead to overestimation.